2010
DOI: 10.1590/s1677-55382010000400005
|View full text |Cite
|
Sign up to set email alerts
|

Endourological Management of Forgotten Encrusted Ureteral Stents

Abstract: Purpose: To present our experience and discuss the various endourological approaches for treating forgotten encrusted ureteral stents associated with stone formation. Materials and Methods: From July 2006 to December 2008, 14 patients (11 men and 3 women) with encrusted ureteral stents were analyzed. The average indwelling time of the stent was 4.9 years (range 1 to 12). Plain-film radiography was used to evaluate encrustation, stone burden, and fragmentation of the stents. Intravenous urogram and a Tc99m diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 31 publications
1
55
0
1
Order By: Relevance
“…Patient and sometimes physician compliance issues lead to stents being forgotten [14]. Poor compliance of the patients represents the main cause [15], which is reflected in our study as well. Proper information and education of the patient regarding the need for stent removal or change is necessary.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Patient and sometimes physician compliance issues lead to stents being forgotten [14]. Poor compliance of the patients represents the main cause [15], which is reflected in our study as well. Proper information and education of the patient regarding the need for stent removal or change is necessary.…”
Section: Discussionsupporting
confidence: 53%
“…A renal scan may be done to document the function. Murthy et al found Bno additional benefit with the use of NCCT^ [15]. In our opinion, NCCT should be done in all the cases where indwelling time is more than 1 year as the stone burden may be radiolucent on plain X-ray.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Recently, multiple endourological approaches and open surgery have been developed to remove the stents in patients with stent-related complications. An endourological procedure is widely accepted for removing ureteral stents, which is more efficient with less wound complications and shorter recovery times than open surgery (6,7). The present study reports a rare case of a patient with a coiled D-J stent which was not removed for 6 years, which resulted in the development of encrustation and was extracted successfully by cystourethroscopy with holmium laser lithotripsy.…”
Section: Introductionmentioning
confidence: 83%
“…[12][13][14][15][16][17][18][19][20] Although there are no formal guidelines in the management of encrusted double-J stents, 15 several authors have reported their series and proposed algorithms: some with multiple sequential surgical techniques; 15,[19][20][21][22][23] others with a one-step approach. 18,24 Even in this single approach technique, after cystolithopaxy or URS in lithotomy position, the patient must be turned prone for PCNL.…”
Section: Introductionmentioning
confidence: 99%